Media sosial untuk meningkatkan kualitas Bahasa Inggris - Rizqiyah, Ni’matur (Maliki Interdisciplinary Journal, 2024)
In today’s digital age, social media has become a dominant tool in communicating and sharing information. This research aims to explore the role of social media in improving English proficiency. The use of platforms such as Tiktok, Instagram, Line, and YouTube can have a significant impact on English language acquisition. This study uses a qualitative method with a case study approach to analyze the experience of learning English through social media. Data was collected through in-depth interviews with participants who actively use social media for language learning purposes. The results show that social media can significantly improve English language skills, especially in the aspects of listening, speaking, reading and writing. In addition, social media also helps users in understanding cultural context and daily language use. In conclusion, social media can be an effective and fun tool in the English language learning process, supporting both formal and informal learning, as well as providing wide access to varied and interactive learning resources.